INTEGRATION OF PROPHETIC VALUES IN EDUCATION AT METRO MUHAMMADIYAH UNIVERSITY - Ardiwansyah, Bayu; Mawangir, Muh.; Abdurrahmansyah, Abdurrahmansyah (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Background: This study is motivated by the need to develop an educational paradigm that not only focuses on character education but also expands its scope by integrating prophetic values into the education system. Purpose: The study examines the implementation of prophetic values (ṣiddīq, amānah, tablīgh, faṭānah) at Universitas Muhammadiyah Metro (UM Metro). Method: Using a qualitative approach and grounded theory methodology, data was collected through interviews, documentation, and observations, and analyzed using Miles & Huberman's interactive model. Result: The findings reveal that prophetic values are integrated into the curriculum through the "mosque of science" model, which incorporates AIK (Al-Islam and Muhammadiyah) courses across all faculties. This research introduces the theory of holistic integrative prophetic-based education, which not only enhances academic performance but also strengthens moral and ethical character in line with Islamic teachings. Conclusion: The recommendations of this study include evaluating the relevance of education, improving lecturer competence, and conducting further research on the impact of prophetic-based education.